Challenges and Opportunities of Integrating ICTs in ELT and Literature Teaching - Sharma, Kamal (Journal of NELTA Gandaki, 2021)
Due to COVID 19, the teaching was switched to online mode, and it is still in practice due to the second and third wave. As a new experience, both teachers and students felt uncomfortable to start online classes. What they lacked was the digital literacy of integrating ICTs in learning, and strong Internet facility. Integration of ICTs into Teaching and Learning during COVID 19 and its aftermath is both obligatory and essential. Education and digital tools are now complementary to each other. This paper aims at looking at the effectiveness of ICTs in teaching English literature, language and examines problems associated with it focusing especially on online classes during COVID. The paper has been conducted through a set of questionnaires designed for teachers and students. The research is conducted through interviews with teachers, and the result identified that problem was not only with the students alone, it was also with the systems including teachers and concerned authorities. The paper concludes that by developing digital literary and ICT skills in students and teachers, the teacher can engage, enrich, enable and empower the students so that the knowledge as envisioned in respective curriculum can be materialized. Within ICTs, MS Teams application used by teachers is the ICT tool that the paper basically focuses on. Recording the class, audio-video setting, cloud video setting, making lesson plans virtually are to be focused while giving training to teachers.